Teaching Modern Macroeconomics in the Mundell-Fleming Language: The IS-MPR-UIP-AD-AS Model - Mendoza Bellido , Waldo (2017)
The traditional open aggregate demand and aggregate supply model backed by the Mundell-Fleming model, together with the supply curve that relates the price level to the output gap, should be abandoned in undergraduate Macroeconomics teaching. First, because economies do not return automatically to equilibrium; second, modern central banks set the interest rate, not the amount of money; and third, the main variable of interest is inflation, not price level. The New Keynesian models taught in intermediate macroeconomics have raised these questions, and had been expected to replace the traditional model. However, they lack its appeal and simplicity. At present, the Mundell-Fleming model, on the verge of turning 60, remains a fundamental part of undergraduate-level macroeconomics textbooks. In this article we present an alternative, the IS-MPR-UIP-AD-AS, a simple New Keynesian model and a form of the Mundell-Fleming with inflation targeting that determines the equilibrium values ​​of production, inflation, the real interest rate, and the real exchange rate. The model is as simple as the traditional one in that it replicates the general equilibrium scheme, it contains a reasonable measure of mathematics and graphical treatment, and it has a simple connection between predictions and facts; but it is also useful in analyzing the main questions of interest. In addition, and more importantly, the device is as flexible as the traditional one, so it can be extended to deal with more complex matters. The main objective is that this model replace the traditional Mundell-Fleming in the teaching of macroeconomics at the undergraduate level. El modelo tradicional de demanda y oferta agregada respaldado por el modelo de Mundell-Fleming y la curva de oferta que relaciona el nivel de precios con la brecha del producto, deberían ser abandonados de la enseñanza de Macroeconomía de pregrado. Primero, porque las economías no regresan automáticamente al equilibrio; en segundo lugar, los bancos centrales modernos controlan la tasa de interés, no la cantidad de dinero; y tercero, la principal variable de interés es la inflación, no el nivel de precios. Los nuevos modelos keynesianos que se enseñan en la macroeconomía intermedia han planteado estas preguntas, y se esperaba que reemplazaran al modelo tradicional. Sin embargo, carecen de su atractivo y simplicidad. En la actualidad, el modelo Mundell-Fleming, a punto de cumplir 60 años, sigue siendo una parte fundamental de los libros de texto de macroeconomía a nivel de pregrado. En este artículo presentamos una alternativa, el IS-MPR-UIP-DA-OA, un nuevo modelo keynesiano simple, una suerte de Mundell-Fleming con metas de inflación, que determinan los valores de equilibrio de la producción, la inflación y el tipo de cambio real. El modelo es tan simple como el tradicional, ya que reproduce el esquema de equilibrio general, contiene una dosis razonable de matemáticas y tratamiento gráfico, y tiene una conexión simple entre predicciones y hechos; pero también es útil para analizar las principales cuestiones de interés. Además, y lo que es más importante, el dispositivo es tan flexible como el tradicional, por lo que puede extenderse para tratar asuntos más complejos. El objetivo es que este modelo sustituya al tradicional Mundell-Fleming en la enseñanza de Macroeconomía a nivel de pregrado.